Improvement of Genetic Transformation Efficiency in Vanda tricolor Orchid Using Acetosyringone - Dwiyani, Rindang; Purwantoro, Azis; Indrianto, Ari; Semiarti, Endang (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2010)
Vanda tricolor Lindl. var. suavis is an Indonesian wild orchid which is now extremely rare in nature due to its habitat destruction. Development of an appropriate method for improving Vanda orchid through genetic modification could be valuable for horticulture and, indirectly, also for conservation. In this research, a method of Agrobacterium-mediated transformation of two Vanda tricolor obtained from Salak Mount, West Java and merapi Mount, Yogyakarta in Indonesia protocorms was improved using acetosyringone (AS). Concentrations of 0 and 25 ppm AS were used in transformation of pG35S binary vector containing kanamycin resistance gene into V. tricolor protocorms. The result showed that 25 ppm AS was required on innoculation with Agrobacterium solution, without AS on cocultivation. Five week s after treatment on the 300 ppm kanamicyncontaining medium, green protocorms were obtained, that was 11.01% for V. tricolor from Salak Mount with pre-culture treatment prior to innoculation, 9.39% for V. tricolor from Merapi Mount with pre-culture treatment prior to innoculation, and 1.37% for V. tricolor from Merapi Mount without pre-culture treatment prior to innoculation. The best condition to set high efficiency of transformation is pre -culture protocorms prior inoculation, soaking protocorm on 25 ppm AS for 30 minutes, then cocultivate its on AS-free callus induction medium Key words: Vanda tricolor, Agrobacterium, orchid protocorms, acetosyringone